STUDI KOORDINASI PRODUKSI PENJUALAN DAN SISTEM PEMBAYARAN ANTARA PRODUSEN DENGAN BEBERAPA DISTRIBUTOR (Studi Kasus di Industri Keramik) - Felecia Felecia; I Gede Agus Widyadana; I Nyoman Pujawan (Institute of Research and Community Outreach - Petra Christian University, 2001)
Coordination is important in industry, so this research try to observe coordination problem which appear at PT'X